FORMULASI KEBIJAKAN TINDAK PIDANA PROSTITUSI ONLINE TERHADAP KORBAN ANAK (ANALISIS PUTUSAN PENGADILAN NEGERI SERANG NOMOR 563/PID.SUS/2023/PN.SRG) - Baity Ramona, Erizka; Lumban Gaol, Selamat (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN RAHMAT HUSADA, 2024)
The development of prostitution with social media intermediaries (online prostitution) is becoming lively, the percentage is increasing and the development is rapid. Prostitution activities have never experienced a degradation in the number of activities, but have always increased in number every year and this is a criminal act with old cases wrapped in a new way due to sophisticated technology. This research is a normative legal research method (Yuridis Normatif). The researcher examines how the regulation of the criminal act of online minor prostitution in Indonesian criminal law and what considerations the Panel of Judges in the Serang District Court Decision Number 563/Pid.Sus/2023/PN.SRG imposed punishment on the defendant. It can be concluded that the regulation of online child prostitution cases in Indonesia gives rise to a vague norm, namely the vagueness of norms because there are laws and regulations whose meaning is unclear and there is no detailed explanation of the existing articles so that they are prone to multiple interpretations. The judge's consideration used in resolving the case was correct because the defendant's actions fulfilled the elements in the indictment. However, the judge overruled several regulations, especially the ITE Law regarding the crime of prostitution through electronic media. It is necessary to systematically re-regulate online prostitution of children, especially in the Criminal Code. This regulation needs to involve good cooperation between the Attorney General, Police, State Cyber and Crypto Agency (BSSN), Communication and Information, Indonesian Child Protection Commission (KPAI), National Human Rights Commission, Ministry of PPA, Ministry of Social Affairs through a memorandum of understanding between these institutions to ensure legal certainty in Indonesia.